An evaluation study of mass drug administration of DEC tablet in a North-Eastern district of Andhra Pradesh - Dash, Satyanarayan; Samantaray, Aurobindo (International Journal Of Community Medicine And Public Health, 2017)
Background: The programme of mass drug administration for elimination of lymphatic filariasis is unique in its strategy that one dose of DEC with or without albendazole has been found to be capable enough to eliminate the load of filariasis worms which might have been built up over a period of one year in the people. So all attempts are really made in filarial endemic areas to administer DEC and albendazole to eligible population for the above purpose. The objective of the study were to review the progress of activities of single dose DEC mass administration in the selected district, make assessment of program implementation and recommend further course of action Methods: A cross – sectional study was done in Vizianagaram district of AP State from 15th March to 15th June 2016. All the PHCs were stratified into 3 groups depending on MDA 2015 coverage. The three categories of the PHCs are identified according to high coverage, very high coverage and very high coverage of DEC consumption. Thus three PHCs and an urban area were selected. Clusters of 30 houses from one village of each PHC and one ward of urban area with a total of 120 households were selected. One respondent from each house was interviewed for the purpose. Results: The age and sex wise distribution of study population for evaluation of MDA in urban area is 55.2% males and 44.8% whereas in rural area it was 54.4% males and 45.6% females. The age and sex distribution of respondents of MDA 2015 DEC evaluation study in urban area was 6.7% males and 93.3% females whereas in rural area it was 14.4% males and 85.6% females. Conclusions: The evaluation study of MDA on DEC clearly shows that there has been overwhelming success in administration and consumption of the drug DEC during MDA activity of 2015.